(Sub)Gev Dark Matter in the U(1)X Higgs Portal Model - Diaz-Saez, B (Elsevier B.V., 2023)
In this research we consider a U(1)X gauge boson acting as a dark matter candidate. The vector dark matter (DM) gets mass when a complex singlet scalar breaks the gauge symmetry spontaneously, adding a second Higgs boson to the spectra. The dark matter candidates communicate with the SM particles via a scalar-Higgs portal. In this work, we concentrate on the masses of the vector dark matter and the scalar mediator below 10 GeV, aka light dark matter. Although we assume thermal freeze-out for the vector DM using the zero-moment of the full Boltzmann equation to calculate the relic abundance, we explore the effects of the second-moment when the vector DM annihilates resonantly. As typically light DM is highly sensitive to CMB bounds, we focus on two thermal mechanisms which alleviate this bound: dark matter annihilation via forbidden channels and near a pole. Other bounds from colliders, thermalization conditions, beam-dump experiments, and astrophysical observations are imposed. Taking into account all the bounds including the direct detection upper limits, the viable space is achieved. © 2023 The Author(s)